(untitled) (Advances in Systems Science and Applications, 2023)
This work focuses on a numerical analysis of fluid-structure thermal coupling in a heating slab. The latter consists of a rectangular cross-section duct located in the concrete slab of a discredited habitat. We modeled the thermal transfers of fluid flow in the pipe. In fact, the Navier-Stokes equations that govern this flow have been solved numerically. These equations were by an implicit method of finite differences. The systems of algebraic equations thus obtained were solved by the algorithms of Gauss and Thomas. The equation of conduction in the concrete slab was solved using the same methodology as that of flow. In this work, we based on an algorithm that interacts non stationary solid medium with a fluid medium consisting of permanent a state by ensuring equal flows and temperatures on the common interface between the two mediums at every moment. The numerical simulation of heat transfers and the thermal behavior of the heating slab were analyzed for various parameters influencing thermal diffusion. The results obtained show that the numerical methodology adopted for the control of fluid-structure coupling is acceptable in comparison with the literature.